2015
DOI: 10.1039/c4sm02256d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvent choice on the gelation and final hydrogel properties of Fmoc–diphenylalanine

Abstract: Gels can be formed by dissolving Fmoc-diphenylalanine (Fmoc-PhePhe or FmocFF) in an organic solvent and adding water. We show here that the choice and amount of organic solvent allows the rheological properties of the gel to be tuned. The differences in properties arise from the microstructure of the fibre network formed. The organic solvent can then be removed post-gelation, without significant changes in the rheological properties. Gels formed using acetone are meta-stable and crystals of FmocFF suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
148
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 34 publications
12
148
0
Order By: Relevance
“…This phase-separation event implies that how the process is carried out will likely determine the outcome of the self-assembly and the gel properties. Again, for related gelators, we have shown that the choice of organic solvent in which the gelator is initially dissolved affects the outcome, 77 which is unsurprising as the solubility of the gelator will be different in each solvent, and different mixing rates of the solvents with water among other variables. Elsewhere, it has been stated that fresh solutions of the gelator in an organic solvent are always prepared to ensure complete dissolution of the LMWG, 73 but this is never actually proven as far as we can see.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…This phase-separation event implies that how the process is carried out will likely determine the outcome of the self-assembly and the gel properties. Again, for related gelators, we have shown that the choice of organic solvent in which the gelator is initially dissolved affects the outcome, 77 which is unsurprising as the solubility of the gelator will be different in each solvent, and different mixing rates of the solvents with water among other variables. Elsewhere, it has been stated that fresh solutions of the gelator in an organic solvent are always prepared to ensure complete dissolution of the LMWG, 73 but this is never actually proven as far as we can see.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…A very illustrative example corresponds to the self-assembly of diphenylalanine (FF), as a minimal sequence to form peptide nanostructures, which organizes forming peptide nanotubes stabilized by a combination of hydrogen bonding and repeated phenyl stacking interactions. [12][13][14] In contrast, Fmoc-FF forms peptide fibrils 15 and very stable hydrogels 9,16,17 that were thought to arise from the stacking between Fmoc groups and between phenyl groups. The remarkable importance of stacking interactions induced by the Fmoc group at the N-terminus was also illustrated using a series of dipeptides and amino acids, 18 such aromatic moiety acting as a consistent facilitator of gelation in comparison to other simple hydrophobic groups, such as tert-butoxycarbonyl.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the presence of gelatinous rounded aggregates is supported by the role played by aromatic end groups as facilitators of gelation. 9,[16][17][18] Accordingly, the majority of the peptide molecules located at the central region of such gelatinous structures could migrate through diffusion towards the external region, allowing the development of the hollow microstructure after solubilization or precipitation of the remaining peptide molecules.…”
mentioning
confidence: 99%
“…the ability to reform after application of high shear. [9][10][11] This ability for recovery after high shear is particularly relevant for injectable gels sheared through a needle as following injection the gel would be required to revert back to its original state. Indeed the self-healing properties of LMWGs is uncommon 12 when compared to the reported self-healing of polymer hydrogels.…”
Section: Introductionmentioning
confidence: 99%